Upaya Membentuk Kemandirian Belajar dan Kemampuan Berpikir Kritis dengan Layanan Konseling Teknik Self Regulated Learning - Qurbi, Abdullah; Diswantika, Noviana; Ningsih, Dita Fitria (STKIP PGRI Bandar Lampung, 2023)
This article focuses on self regulated learning techniques, as an effort to form independence learning and critical thinking skills in student. Indonesian students are independent students, students who are responsible for the learning process and learning outcomes. Apart from having independence in learning, indonesian students are also students who reason crtically, that is able to objectively process information, able to create linkages between various information, able to analyze various information, able to evaluate and counclude information. The writing method is a literature studi (review). Data and informations obtained derived from various reading sources and compiled based on the results of studies from data and the informations obtained. Data analysis technique is descriptive argumentative. Writing done by looking at the interrelationhips and synchronization between data and informations one with data and informations other informations according to the topic under study. Self regulated learning techniques for students are the ability to develop self directed learning and critical thinking skills students. In an effort to from independent learning and critical thinking skill in students one of them is academic counseling. The self regulated learning technique helps students develop a more effective way of learning, helping students to succeed in learning and able to adapt to all the demands of education.